Childhood central nervous system tumour mortality and survival in Southern and Eastern Europe (1983–2014): Gaps persist across 14 cancer registries. Issue 17 (November 2015) - Karalexi, Maria A.; Papathoma, Paraskevi; Thomopoulos, Thomas P.; Ryzhov, Anton; Zborovskaya, Anna; Dimitrova, Nadya; Zivkovic, Snezana; Eser, Sultan; Antunes, Luís; Sekerija, Mario; Zagar, Tina; Bastos, Joana; et al.
Highlights: Variations in CNS tumour survival/mortality are noted across Southern–Eastern Europe. Survival declines fastest before the 2nd year of follow-up. Rural residence has an adverse effect on the survival of childhood CNS tumours. International disparities may reflect economic growth/health-delivery inequalities. Continuous cancer registration and follow-up favour reduction of survival disparities. Abstract: Aim: Childhood central nervous system (CNS) tumour registration and control programs in Southern and Eastern Europe remain thin, despite the lethal nature of the disease. Mortality/survival data were assembled to estimate the burden of malignant CNS tumours, as well as the potential role of sociodemographic survival determinants across 14 cancer registries of this region. Methods: Average age-adjusted mortality rates were calculated, whereas time trends were quantified through Poisson and Joinpoint regressions. Kaplan–Meier curves were derived for the maximum and the more recent (10 and 5 year) registration periods. Multivariate Cox regression models were used to assess demographic and disease-related determinants. Results: Variations in mortality (8–16 per million) and survival (5-year: 35–69%) were substantial among the participating registries; in most registries mortality trend was stable, whereas Bulgaria, having the highest starting rate, experienced decreasing annual mortality (−2.4%, p  = 0.001). A steep decrease in survival rates was evident before the second year of follow-up. After controlling for diagnostic subgroup, age, gender and diagnostic year, Greece seemed to present higher survival compared with the other contributing registries, although the follow-up period was short. Irrespective of country, however, rural residence was found to impose substantial adverse repercussions on survival (hazard ratio (HR): 1.2, 95% confidence interval (CI): 1.1–1.4). Conclusion: Cross-country mortality and survival variations possibly reflect suboptimal levels of health care delivery and cancer control in some regions of Southern and Eastern Europe, notwithstanding questionable death certification patterns or follow-up procedures. Continuous childhood cancer registration and linkage with clinical data are prerequisite for the reduction of survival inequalities across Europe.